(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To comments factors associated with the degree of oligohydramnios and pregnancy outcomes among affected women. Subjects and methods: A retrospective descriptive study was conducted on 142 pregnant women diagnosed with oligohydramnios at Hanoi Obstetrics and Gynecology Hospital. Results: Mild oligohydramnios accounted for the highest proportion (44.37%). Factors significantly associated with the degree of oligohydramnios included maternal age (p = 0.049), gestational age (p = 0.000), and fetal risk factors (p = 0.000). Severe oligohydramnios was more common in women aged 25-29 years (40.74%), with gestational age < 28 weeks (59.3%), and in fetuses with combined abnormalities (55.56%). The most frequent structural abnormalities were gastrointestinal (17.61%) and cardiovascular (15.49%) malformations. In the group with anhydramnios, the rates of pregnancy termination and intrauterine fetal death were significantly higher (14.81%), with a statistically significant difference (p = 0.010). Conclusion: Mild oligohydramnios accounted for the highest proportion. Maternal age, gestational age, and certain maternal and fetal conditions that increase pregnancy risk were significantly associated with the severity of oligohydramnios. The most common fetal structural abnormalities were observed in the gastrointestinal and cardiovascular systems. The more severe the oligohydramnios, the higher the likelihood of adverse pregnancy outcomes.